2010
DOI: 10.1021/om100505w
|View full text |Cite
|
Sign up to set email alerts
|

Novel Synthesis of Chiral 1,3-Diphosphines via Palladium Template Promoted Hydrophosphination and Functional Group Transformation Reactions

Abstract: A novel cyano-functionalized monophosphine palladium substrate containing the ortho-metalated (R)-(1-(dimethylamino)ethyl)naphthalene as the chiral auxiliary was synthesized from 3-chloropropionaldehyde diethylacetal via a one-pot process. The asymmetric hydrophosphination reactions between diphenylphosphine and the trans-or cis-monophosphine substrates were carried out under mild conditions, which gave the corresponding cyano-substituted chiral 1,3-bis(diphenylphosphino)propane palladium complexes with good y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…In principle, asymmetric HP is an incredibly powerful synthetic route to access the next generation of chiral phosphine ligands. This area of HP has been dominated by palladium complexes bearing chiral chelating auxiliaries. However, there have been early examples of nickel-catalyzed , and organocatalytic asymmetric HP. More recently Wang and co-workers reported the asymmetric HP of numerous azabenzonorbornadiene and oxabenzonorbornadiene substrates with different secondary biarylphosphines mediated by palladium precatalyst and Fe­(OAc) 2 as a substoichiometric additive (Scheme ).…”
Section: Hydrophosphinationmentioning
confidence: 99%
“…In principle, asymmetric HP is an incredibly powerful synthetic route to access the next generation of chiral phosphine ligands. This area of HP has been dominated by palladium complexes bearing chiral chelating auxiliaries. However, there have been early examples of nickel-catalyzed , and organocatalytic asymmetric HP. More recently Wang and co-workers reported the asymmetric HP of numerous azabenzonorbornadiene and oxabenzonorbornadiene substrates with different secondary biarylphosphines mediated by palladium precatalyst and Fe­(OAc) 2 as a substoichiometric additive (Scheme ).…”
Section: Hydrophosphinationmentioning
confidence: 99%
“…The effective catalysis of hydroamination, hydrosilylation, and hydrophosphination is very attractive, due to the 100% atom economy involved in these reactions . In contrast to the myriad reported catalysts for hydroamination and hydrosilylation reactions, the number of known hydrophosphination catalysts remains small, although they span the entire periodic table, with several reports involving late transition metals. , Early-metal catalysts, such as those of Waterman and Mindiola, have been utilized in the intermolecular hydrophosphination of alkynes. , Main-group metals can also be effective, as noted in Cui, Stephan, and Hill’s reports on alkali-metal- and alkaline-earth-metal-catalyzed hydrophosphination reactions. ,, Furthermore, the Marks and Hou groups have shown that even f elements can be employed, as demonstrated in the hydrophosphination of olefins and carbodiimides using constrained-geometry lanthanide catalysts. , We were especially intrigued by the use of lanthanides, due to the various possible advantages available with these metals, such as their electrophilicities, the ability to tune the steric environment about these metal centers through a proper choice of supporting ligands, and their absence of unproductive oxidative addition/reductive elimination reaction pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Asymmetric hydrogenation, by employing the clean molecular hydrogen to reduce the prochiral C=C, C=O, and C=N double bonds, is probably one of the most simplest and powerful method to produce a myriad of chiral amino acid derivatives, chiral alcohols, and chiral amines, which are important building blocks for organic synthesis. 4,5 The pioneer work was presented in 1971 by Kagan, 6 who developed the first chiral diphosphine ligand, DIOP, derived from tartaric acid, for rhodium-catalized asymmetric hydrogenation reactions with high enantioselectivities. Knowles made his significant contribution by discover a P-chiral diphosphine, DIPAMP, in 1975.…”
Section: Asymmetric Hydrogenation Reactionmentioning
confidence: 99%
“…is smaller than its counterpart in complex 37a, resulting in a relative larger bite angle (85.1(1)°), and the angles around the metal center are in the ranges of of 80.5(1) -99.8 (1) and 174.4(1) -178. 4(1)°. The newly formed stereogenic center at C27 adopts the S absolute configuration with the keto functionality occupying the sterically favorable equatorial position.…”
Section: Asymmetric Hydrophosphination Of Coordinated 5-(diphenylphosmentioning
confidence: 99%
See 1 more Smart Citation